Perlindungan Konsumen Pakaian Bayi Tidak Berstandar Nasional Indonesia di Kota Banda Aceh - Nining Aja Liza Wahyuni; Rofah Setyowati; Muchlas Rastra Samara (PROGRESIF: Jurnal Hukum, 2020)
Positive law in Indonesia stipulates that business actors are not allowed to produce and trade all products, including baby clothes that do not meet the Indonesian National Standard (SNI). However, in reality, baby clothing business actors still find violations, for example, in the city of Banda Aceh. Departing from these problems, this study aims to explain the role of the government in protecting consumers. These factors cause the sale and purchase of baby clothes that do not have SNI and legal measures that consumers can take as a form of responsibility for sellers of baby clothes who do not have SNI. This research is legal research that is juridical and empirical that seeks newness based on field research concerning legitimate science. Field research was conducted to obtain primary data through interviews and provide questionnaires with respondents and informants. Based on the results of the study, it is known that the role of the government in protecting consumers has carried out supervision, established several regulations and conducted socialization regarding mandatory SNI for baby clothes that are not SNI but not yet fully effective.